2013
DOI: 10.1111/1467-9566.12100
|View full text |Cite
|
Sign up to set email alerts
|

Actors, patients and agency: a recent history

Abstract: This article examines the history of patients' behaviour since the middle of the 20(th) century. It describes a number of strategies that have served to encourage patients to exercise increasingly autonomous behaviour. The effect has been to instil a sense of agency in previously passive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 56 publications
3
67
0
3
Order By: Relevance
“…On a theoretical front, we would argue that the talk of our respondents reflects on central features of what sociologists have referred to as the structure/agency debate (Armstrong, 2014;Giddens, 1984). This is especially in so far as such talk so clearly connects individual 'behaviour' to civic, social, political and physical structures far more strongly than to motives and personal preferences.…”
Section: And I Know It's Not Your (Ie the Moderator's) Remit But Imentioning
confidence: 99%
“…On a theoretical front, we would argue that the talk of our respondents reflects on central features of what sociologists have referred to as the structure/agency debate (Armstrong, 2014;Giddens, 1984). This is especially in so far as such talk so clearly connects individual 'behaviour' to civic, social, political and physical structures far more strongly than to motives and personal preferences.…”
Section: And I Know It's Not Your (Ie the Moderator's) Remit But Imentioning
confidence: 99%
“…Pasienter forstås dermed som å ha «agency», dvs. muligheten for individuell, selvstendig handling (Armstrong, 2014), i stedet for å vaere objekter mer eller mindre prisgitt helsepersonells vurderinger og beslutninger. Dette innebaerer ifølge Armstrong (2011) at pasienter har gått fra å tidligere ha sykdom til nå i større grad å erfare/oppleve sykdom.…”
Section: Individualisering Som Medbestemmelseunclassified
“…Standardisering forbindes, som tidligere beskrevet, ofte med noe kjedelig, likt og undertrykkende for individuelle uttrykk, som noe entydig determinerende og dehumaniserende (Timmermans og Epstein, 2010). Individualisering knyttes derimot ofte til noe som er frigjørende for individet, hvor pasienter forstås som å ha mulighet for selvstendig handling i stedet for å vaere objekter underlagt helsepersonells kontroll (Armstrong, 2014). Vi ser i våre tekster at forståelsene av standardisering og individualisering beskrevet over, delvis skrives frem på lignende måter og delvis skrives frem på helt andre måter -og at forståelsen også skifter i løpet av tekstenes ulike deler.…”
Section: God Pasientbehandling Som Standardisering Og Individualiseringunclassified
“…The management and control of patient choices and practices through cultural and institutional means has been a mainstay of health sociology since Talcott Parsons' investigations into the 'sick role' (Willis, 2015;Armstrong, 2013). Sociologists have demonstrated that individual choices and experiences are partly the consequence of the knowledge they bring to their interactions with healthcare practitioners, but these interactions are themselves structured and constrained by widespread public discourses about healthcare, as well as by the organisation of the healthcare setting itself, for instance by its payment systems (Shim, 2010).…”
Section: Introductionmentioning
confidence: 99%